Accuracy of a flash glucose monitoring system in cats and determination of the time lag between blood glucose and interstitial glucose concentrations. (15th May 2021) - Del Baldo, Francesca; Fracassi, Federico; Pires, Jully; Tardo, Antonio Maria; Malerba, Eleonora; Manassero, Elisa; Gilor, Chen
Abstract: Background: The FreeStyle Libre (Abbott Laboratories) is a flash glucose monitoring system (FGMS) that measures interstitial glucose concentration (IG). The system is factory‐calibrated, easy to use, inexpensive, and could be useful for monitoring diabetic cats. Objectives: To evaluate the analytical and clinical accuracy of the FGMS in cats and establish the lag‐time between IG and blood glucose concentration (BG). Animals: Twenty client‐owned diabetic cats and 7 purpose‐bred healthy cats. Methods: Prospective study. Blood glucose concentration was measured using a portable glucose meter validated for use in cats that served as a reference method for IG, as measured by FGMS. In diabetic cats, data were collected for sensor wearing time with different methods of application and accuracy across glycemic ranges. Accuracy was determined by fulfillment of ISO15197:2013 criteria. In healthy cats, lag‐time between IG and BG was established after IV administration of exogenous glucose. Results: Good agreement between IG and BG was obtained ( r = .93). Analytical accuracy was not achieved, whereas clinical accuracy was demonstrated with 100% of the results in zones A + B of the Parkes consensus error grid analysis. In the immediate 30 minutes after an IV bolus of glucose, when BG was increasing rapidly (approximately 2%/min), IG increased slowly, resulting in a difference of as much as 579 mg/dL, and no positive correlation between BG and IG was found. Conclusions and Clinical Importance: The FGMS did not fulfill ISO requirements but is sufficiently accurate for glucose monitoring in cats, while considering the lag between IG and BG during periods of rapid changes in BG.